KAJIAN PERUBAHAN GARIS PANTAI DENGAN MENGGUNAKAN TEKNOLOGI PENGINDRAAN JAUH DI WILAYAH PESISIR KECAMATAN SINJAI TIMUR, KABUPATEN SINJAI - Irfan Fauzi; Danial Danial; Abdul Rauf (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
Coastal is the meeting area between land and sea. This study aimed to (1) calculate how much shoreline change in East Sinjai Sub-district (2) analyze the factors that influence changes in the coastline in East Sinjai District (3) formulate strategic directions for shoreline change management in East Sinjai Sub-district. Citra data processing method used Er-Mappaer and Arcgis, and management strategy direction used SWOT analysis. The results of citra interpretation showed that the shoreline change in abrasion was 9.73 Ha and accretion was 20.39 Ha. The factors that caused the changes in the coastline included waves, currents, tides and conditions of the coastal ecosystem in East Sinjai Sub-district. In the coastal management analysis, there were 4 management strategies; determined coastal conservation areas as a measure to control abrasion and sedimentation, developed strategies that referred to ICM (integrated Coastal Management), improved the quality and awareness of human resources on coastal environmental management and law enforcement and institutional strengthening in coastal management. The use of high-resolution citra required further research by adding parameters such as the type of substrate and sedimentation rate. For the government of Sinjai District to conduct a study on mitigation of coastal abrasion and sedimentation disasters.